Green Human Resource Management Model and Subject Well Being Towards Sustainability Performance - Suryani, Herni; Agustina, Granit; Ahmadi, Rudi Suprianto; Febrian, Feby (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of green human resource management, subject well being and sustainability performance. The method used in this study is quantitative with a descriptive and verification approach. Primary data collection techniques were obtained through questionnaires, observations and interviews. Secondary data were obtained through libraries and reviewed documents. The population of this study were 100. Multiple linear regression analysis or path analysis was used. It turned out that green human resource management and subject well being on sustainability performanceas a whole showed a positive and good response. It can be concluded that there is a fairly strong influence between green human resource management and subject well being on sustainability performance and others are influenced by other factors.